Implementation Analytical Hierarchy Process Method to Improve the Effectiveness of Social Assistance Distribution - Sari, Yunita Sartika; Hakim, Lukman (Journal Collabits, 2024)
Based on the report of the central statistics agency, the number of poor people in Indonesia reached 26.16 million people. The government has made efforts to provide assistance to overcome this problem, one of which is beneficiaries. The distribution of beneficiaries which is being held is still not optimal because of the uneven distribution of aid to underprivileged communities. The purpose of this research is to implement a Decision Support System (DSS) to determine the right community to receive beneficiaries which will be given based on several criteria used, namely: education, employment, and place of residence. In this study, proposes to build a model that has a decision-making concept. The method used in this Decision Support System is the Analytical Hierarchy Process (AHP). The expected results in this study are a decision support system that can assist in determining beneficiaries.